High-strength 7xxx series aluminum alloy capable of being anodized and preparation method of high-strength 7xxx series aluminum alloy

By controlling the grain size and second phase precipitation, a high-strength 7xxx series aluminum alloy that can be anodized is prepared by using specific process methods, solving the problems of yellowing color, numbness on the surface and large gloss deviation after anodization, achieving better highlight effect and higher performance.

CN119663079APending Publication Date: 2025-03-21FUJIAN XIANGXIN CORP LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411615295.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing 7xxx series aluminum alloys have problems such as yellowing, numbness on the surface and large gloss deviation after anodization treatment, making it difficult to maintain highlight effects and performance.

Method used

By controlling the grain size and second phase precipitation, high-strength 7xxx series aluminum alloys that can be anodized are prepared by controlling specific aluminum alloy components and trace elements, heat treatment technology of ingots, hot extrusion and heat treatment, anodization process and sealing treatment.

Benefits of technology

It has achieved better highlight effect and higher performance after anodization treatment of 7xxx aluminum alloy, avoiding yellowing, numbness on the surface and large gloss deviation, and improving the product's performance and market prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119663079A_ABST
    Figure CN119663079A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength 7xxx series aluminum alloy capable of being anodized and a preparation method thereof. The high-strength 7xxx series aluminum alloy capable of being anodized comprises the following components: less than 0.07% of silicon, less than or equal to 0.12% of iron, 1.2-1.6% of copper, 0.07-0.17% of manganese, 2.10-2.40% of magnesium, 0.003-0.012% of zirconium, 6.2-6.5% of zinc, less than or equal to 0.003-0.020% of titanium and the balance of aluminum and other inevitable impurity elements. The preparation method of the high-strength 7xxx series aluminum alloy capable of being anodized comprises the steps of smelting and casting, homogenizing treatment, hot extrusion and heat treatment and anodizing treatment. A 7xxx series aluminum alloy product prepared through the preparation method has good intergranular corrosion and exfoliation corrosion performance; according to the alloy performance, the tensile strength is larger than or equal to 480 MPa, the yield strength is larger than or equal to 450 MPa, and the ductility is larger than or equal to 9%; in the grain sizes of the profile, the average grain size is less than or equal to 150 microns, and the maximum grain size is less than or equal to 250 microns; and after anodic oxidation treatment, the polishing glossiness is larger than 450 GU, more obvious advantages are achieved, and the good market prospect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to an anodizable high-strength 7xxx series aluminum alloy and a preparation method thereof. Background Art

[0002] 6xxx series aluminum alloys are widely used in the manufacture of 3C product appearance parts due to their high strength and good anodizing effect. With the improvement of industry requirements and technological progress, higher strength requirements are put forward for performance. In order to gradually replace the original 6xxx series aluminum alloys, the upgraded 7xxx series alloys are gradually being used in 3C products.

[0003] 7xxx series alloys, also known as super duralumin, are a series of heat-treatable aluminum alloys based on aluminum-zinc-magnesium-copper, with high specific strength, high specific stiffness, high toughness, excellent processing performance and welding performance. These alloys are widely used in aircraft frames, wing spars and longitudinal beams and other bearing components, and are one of the most important structural materials in the aviation field. 7xxx series alloys are strengthened by heat treatment processes, including solution treatment, quenching and aging treatment. Solution treatment is to heat the alloy to a certain temperature to dissolve the strengthening phase, quenching is to quickly cool to fix these phases, and aging treatment is carried out at a lower temperature to promote the precipitation of finer and more uniform strengthening phases; in addition, the existing 7xxx series alloy products have yellowing color, numbness on the surface, and large gloss deviation after anodizing.

[0004] 3C products usually need to be oxidized to achieve a high-gloss effect, and the size of the aluminum alloy grains and the precipitation of the second phase play a decisive role in the effect after oxidation. In order to obtain a better appearance effect, the current requirement is to ensure that the average grain size of the aluminum alloy ingot and subsequent extrusion material is less than 150μm. In order to ensure that the 7xxx series alloy has a better high-gloss effect under anodization and maintains higher performance, the present invention proposes an anodizable high-strength 7xxx series aluminum alloy and a preparation method thereof. Summary of the invention

[0005] (1) Technical issues to be solved

[0006] The purpose of the present invention is to provide a high-strength 7xxx series aluminum alloy that can be anodized and a preparation method thereof, which overcomes the problem that the high-strength 7xxx series aluminum alloy that can be anodized prepared by the traditional method in the prior art can maintain its high gloss state and performance. The high-strength 7xxx series aluminum alloy that can be anodized and the preparation method thereof in the present invention can improve the 7xxx series aluminum alloy while maintaining higher performance while ensuring the high gloss effect, which is conducive to the accelerated development of the 7xxx series aluminum alloy field.

[0007] (2) Technical solution

[0008] In order to solve the above technical problems, the first aspect of the present invention provides:

[0009] An anodizable high-strength 7xxx series aluminum alloy, the anodizable high-strength 7xxx series aluminum alloy comprising the following components:

[0010] Silicon <0.07%, iron ≤0.12%, copper 1.2-1.6%, manganese 0.07-0.17%, magnesium 2.10-2.40%, zirconium 0.003-0.012%, zinc 6.2-6.5%, titanium 0.003-0.020%, and the balance is aluminum and other inevitable impurity elements; the total mass of other inevitable impurity elements does not exceed 0.15% of the total mass of the alloy.

[0011] The second aspect of the present invention provides:

[0012] A method for preparing an anodizable high-strength 7xxx series aluminum alloy comprises the following steps:

[0013] 1) Melting and casting: ① Melting master alloy: Prepare materials according to the mass percentage of silicon <0.07%, iron ≤0.12%, copper 1.2-1.6%, manganese 0.07-0.17%, magnesium 2.10-2.40%, zirconium 0.003-0.012%, zinc 6.2-6.5%, titanium ≤0.003-0.020% and the balance is aluminum to obtain smelting metal, wherein zinc, aluminum and magnesium are pure zinc ingots, high-purity low-iron aluminum ingots and pure Magnesium ingots, copper, manganese, zirconium and titanium use aluminum-copper master alloy, aluminum-manganese master alloy, aluminum-zirconium master alloy and aluminum-titanium-boron master alloy; high-purity low-iron aluminum ingots are loaded into the furnace, and the furnace gas temperature is set to 750-780°C. After the high-purity low-iron aluminum ingots are melted, slag is removed, and then other master alloys except aluminum-titanium-boron master alloy and pure magnesium ingots are added and wait for them to be completely melted. After the charge is melted, the temperature is 735-745°C. After slag removal, pure magnesium ingots are added and stirred;

[0014] ② Raise the temperature to 780-790℃, use high-purity argon and sodium-free refining agent for refining for 10-15 minutes, then skim and let stand;

[0015] ③ After the casting temperature reaches 740-750°C, casting begins, and aluminum-titanium-boron master alloy wire is fed to obtain an ingot;

[0016] 2) Homogenization treatment: the ingot in step 1) is homogenized by a homogenization process, the temperature of the first stage is set to 300-320°C, the time is 1-2h; the temperature of the second stage is set to 400-420°C, the time is 1-2h; the temperature of the third stage is set to 460-480°C, the time is 10-12h; the third stage homogenization is carried out after strong wind cooling to obtain a homogenized ingot, the average grain size of the cast rod structure is ≤150μm, and the maximum grain size is ≤200μm;

[0017] 3) Hot extrusion and heat treatment: The homogenized ingot in step 2) is heated and extruded. In the extrusion process, the ingot temperature is 460-480°C using a rod casting furnace for preheating and an induction heating furnace. The extrusion speed is set at 0.8-1.5 mm / s, and the outlet temperature is set to be greater than 510°C. The extrusion is then cooled by water cooling to obtain an extruded profile. The cross-sectional dimensions of the extruded sheet are as follows: 70-140 mm in length, 8-3 mm in width, and 0.25-1 mm in R angle.

[0018] 4) Anodizing treatment: ① Degreasing treatment: Use alkaline solution for degreasing, use 40-50g / L sodium carbonate, 40-50g / L sodium phosphate, 80-100g / L sodium pyrophosphate, 0.1-0.5g / L OP-10 surfactant content to prepare an alkaline solution, put the product in step 3) into a cleaning tank containing the alkaline solution, raise the temperature of the solution in the cleaning tank to 40-60°C, and set the degreasing time to 3-8 minutes;

[0019] The degreased product is subjected to multiple water washing operations;

[0020] ② Neutralization and light extraction: After water washing, put it into a nitric acid cleaning tank with a concentration of ≥100g / l, set the neutralization reaction time to ≥30s, and operate at room temperature;

[0021] The product after neutralization and light treatment is subjected to multiple water washing operations;

[0022] ③ Anodizing: Use sulfuric acid as the electrolyte and use a constant voltage method for anodizing. Set the voltage in the flow tank to 12-14V, and limit the concentration of aluminum ions to ≦18g / L, the concentration of free H2SO4 to between 190-200g / L, set the tank temperature to 20±2℃, and set the oxidation time to 50-60 minutes;

[0023] The product after the above steps is subjected to multiple water washing operations;

[0024] ④ Sealing treatment: Add the washed product into the sealing tank and add the tank liquid, which contains: Ni 2+ :1.05-1.45g / l,F -: 0.35-0.50g / l, set the bath solution pH to 5.8-6.4, and use room temperature sealing. In this step, nickel ions are hydrolyzed in the oxide film to seal the holes;

[0025] The product after the above sealing treatment is subjected to multiple water washing operations to obtain the final product.

[0026] Preferably, in step 1), the wire feeding speed of the aluminum-titanium-boron master alloy is 0.8-1.2 m / min, the water flow rate is 1000-1500 L / min, and the water temperature is 25-30° C. It should be noted that during the casting process, a large amount of water is required for cooling to ensure the formation of the cast rod.

[0027] Preferably, in step 1), the casting speed is set differently according to different casting specifications. When the casting rod specification is φ292, the casting speed is 50-55mm / min; when the specification is φ234, the casting speed is 70-75mm / min; when the specification is φ178, the casting speed is 85-90mm / min.

[0028] Preferably, in step 3), the water cooling temperature used in the water cooling method is ≤50°C, and the aging system is set to: 130-145°C*10-24h.

[0029] Preferably, the temperature of sulfuric acid in step 4) is controlled within 20±2° C., and the reaction time of this step is 50-60 min.

[0030] Preferably, in the sealing treatment operation, the sealing time is set to 10-20 minutes, and the temperature during the sealing process is set to 28-35°C.

[0031] Preferably, after hot extrusion and heat treatment operations, the tensile strength of the profile is ≥480MPa, the yield strength is ≥450MPa, and the elongation is ≥9%.

[0032] Preferably, after hot extrusion and heat treatment, the average grain size of the profile is ≤150 μm, and the maximum grain size is ≤250 μm.

[0033] Preferably, in step 4), the surface gloss of the profile after anodizing treatment needs to reach 450-500GU; after oxidation film formation, the film thickness needs to reach 8-15μm, and the surface of the sample is not dull, numb, or discolored to be qualified.

[0034] (3) Beneficial effects

[0035] The invention achieves the requirements of strength and oxidation high gloss by controlling the grain size and second phase precipitation, including the control of aluminum alloy composition and trace elements, heat treatment process of ingot casting, hot extrusion and heat treatment, anodizing process and sealing treatment, etc., thanks to the melt purification device and technology of aluminum alloy, the metallurgical quality of aluminum alloy products can be effectively improved, and the aluminum alloy ingot obtains grains with uniform size from the surface to the center, and the ingot grain size is less than 150μm, which improves the final use performance of the product; the produced 7xxx series aluminum alloy has good intergranular corrosion and exfoliation corrosion performance; in terms of alloy performance, it can achieve: tensile strength ≥480MPa, yield strength ≥450MPa, elongation ≥9%; in the profile grain size, the average grain size is ≤150μm, and the maximum grain size is ≤250μm; and after anodizing treatment, the polishing glossiness reaches >450GU; after oxidation film formation, the surface of the sample has no fogging, numbness, or discoloration. The common problems of yellowing color, surface numbness and large glossiness deviation after anodizing of traditional 7xxx series alloys are solved. Through the preparation method of the present invention, the 7xxx series aluminum alloy has better highlight effect and higher performance under anodizing. Compared with the traditional 6xxx series aluminum alloy and the 7xxx series aluminum alloy with poor effect after anodizing, it has more obvious advantages and better market prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a schematic diagram of the overall operation steps of a method for preparing an anodizable high-strength 7xxx series aluminum alloy.

[0037] Figure 2 This is a schematic diagram of the operating steps in the anodizing process in the method for preparing an anodizable high-strength 7xxx series aluminum alloy of the present invention. DETAILED DESCRIPTION

[0038] The present invention is described in detail below using different manufacturing processes. The enumerated embodiments can enable technicians in this field to better understand the present invention, but do not limit the present invention in any form. For example, the present invention can be expanded to the production of aluminum alloys of other strengths or other alloys with the same characteristics for application.

[0039] Embodiment 1:

[0040] A method for preparing an anodizable high-strength 7xxx series aluminum alloy comprises the following steps:

[0041] 1) Melting and casting: ① Melting master alloy: prepare materials according to mass percentage of copper 1.6%, manganese 0.17%, magnesium 2.40%, zirconium 0.012%, zinc 6.5%, titanium 0.020% and the balance aluminum to obtain smelting metal, wherein zinc, aluminum and magnesium are pure zinc ingots, high-purity low-iron aluminum ingots and pure magnesium ingots, and copper, manganese, zirconium and titanium are aluminum-copper master alloys, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium-boron master alloys; high-purity low-iron aluminum ingots are charged into a furnace, and the furnace gas temperature is set to 750-780° C. After the high-purity low-iron aluminum ingots are melted, slag is removed, and then other master alloys except the aluminum-titanium-boron master alloy and pure magnesium ingot are added and wait for them to be completely melted. After the charge is melted, the temperature is 735-745° C. After slag removal, pure magnesium ingots are added and stirred;

[0042] ② Raise the temperature to 780-790℃, use high-purity argon and sodium-free refining agent for refining for 10-15 minutes, then skim and let stand;

[0043] ③ After the casting temperature reaches 740-750°C, casting begins, and aluminum-titanium-boron master alloy wire is fed to obtain an ingot;

[0044] Among them, the wire feeding speed of aluminum-titanium-boron master alloy is 1.2m / min, the water flow rate is 1500L / min, and the water temperature is 25°C. During the casting process, a large amount of water is required for cooling to ensure the formation of the cast rod, and the casting speed is set differently according to different casting specifications. When the cast rod specification is φ292, the casting speed is 50-55mm / min; the specification is φ234, the casting speed is 70-75mm / min; the specification is φ178, the casting speed is 85-90mm / min.

[0045] 2) Homogenization treatment: The ingot in step 1) is homogenized by a homogenization process, and the temperature of the first stage is set to 320°C and the time is 2 hours; the temperature of the second stage is set to 410°C and the time is 1.5 hours; the temperature of the third stage is set to 480°C and the time is 12 hours; the third stage homogenization is carried out after strong wind cooling to obtain a homogenized ingot.

[0046] 3) Hot extrusion and heat treatment: The homogenized ingot in step 2) is heated and extruded. In the extrusion process, a rod casting furnace is used for preheating and an induction heating furnace is used for heating to an ingot temperature of 460-480°C. The extrusion speed is set at 0.8-1.5 mm / s, and the outlet temperature is set to be greater than 510°C. Then, the ingot is cooled by water cooling, and the water temperature of the water cooling method is ≤50°C. Then, an extruded profile is obtained. The cross-sectional dimensions of the extruded sheet are in the range of: length 70-140 mm, width 8-3 mm, R angle 0.25-1 mm, and aging system: 130-145°C*10-24h.

[0047] 4) Anodizing treatment: ① Degreasing treatment: Use alkaline solution for degreasing, use 50g / L sodium carbonate, 50g / L sodium phosphate, 100g / L sodium pyrophosphate, 0.5g / L OP-10 surfactant content to prepare an alkaline solution, put the product in step 3) into a cleaning tank containing the alkaline solution, raise the temperature of the solution in the cleaning tank to 40-60°C, and set the degreasing time to 3-8 minutes;

[0048] The degreased product is subjected to multiple water washing operations;

[0049] ② Neutralization and light extraction: After water washing, put it into a nitric acid cleaning tank with a concentration of ≥100g / l, set the neutralization reaction time to ≥30s, and operate at room temperature;

[0050] The product after neutralization and light treatment is subjected to multiple water washing operations;

[0051] ③ Anodizing: Use sulfuric acid as the electrolyte and use a constant voltage method for anodizing. Set the voltage in the flow tank to 12-14V, and limit the concentration of aluminum ions to ≦18g / L, the concentration of free H2SO4 to between 190-200g / L, set the tank temperature to 20±2℃, and set the oxidation time to 50-60 minutes;

[0052] The product after the above steps is subjected to multiple water washing operations;

[0053] ④ Sealing treatment: Add the washed product into the sealing tank and add the tank liquid, which contains: Ni 2+ :1.45g / l,F - : 0.50g / l, set the bath pH to 6.4, and use room temperature sealing. In this step, nickel ions are sealed in the oxide film by hydrolysis. The sealing time is 20 minutes, and the temperature during the sealing process is set to 28-35°C;

[0054] The product after the above sealing treatment is subjected to multiple water washing operations to obtain the final product.

[0055] Embodiment 2:

[0056] A method for preparing an anodizable high-strength 7xxx series aluminum alloy comprises the following steps:

[0057] 1) Melting and casting: ① Melting master alloy: prepare materials according to mass percentage of copper 1.2%, manganese 0.07%, magnesium 2.10%, zirconium 0.003%, zinc 6.2%, titanium 0.003% and the balance of aluminum to obtain smelting metal, wherein zinc, aluminum and magnesium are pure zinc ingots, high-purity low-iron aluminum ingots and pure magnesium ingots, and copper, manganese, zirconium and titanium are aluminum-copper master alloys, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium-boron master alloys; high-purity low-iron aluminum ingots are charged into a furnace, and the furnace gas temperature is set to 750-780°C. After the high-purity low-iron aluminum ingots are melted, slag is removed, and then other master alloys except the aluminum-titanium-boron master alloy and pure magnesium ingot are added and wait for them to be completely melted. After the charge is melted, the temperature is 735-745°C, and after slag removal, pure magnesium ingots are added and stirred;

[0058] ② Raise the temperature to 780-790℃, use high-purity argon and sodium-free refining agent for refining for 10-15 minutes, then skim and let stand;

[0059] ③ After the casting temperature reaches 740-750℃, casting begins, and wire feeding of the Rt-Ti-B master alloy is performed to obtain an ingot;

[0060] Among them, the wire feeding speed of aluminum-titanium-boron master alloy is 0.8m / min, the water flow rate is 1000L / min, and the water temperature is 30℃. During the casting process, a large amount of water is required for cooling to ensure the formation of the cast rod, and the casting speed is set differently according to different casting specifications. When the cast rod specification is φ292, the casting speed is 50-55mm / min; the specification is φ234, the casting speed is 70-75mm / min; the specification is φ178, the casting speed is 85-90mm / min.

[0061] 2) Homogenization treatment: The ingot in step 1) is homogenized by a homogenization process, and the temperature of the first stage is set to 300°C and the time is 1.5 hours; the temperature of the second stage is set to 420°C and the time is 1 hour; the temperature of the third stage is set to 460°C and the time is 10 hours; the third stage homogenization is carried out after strong wind cooling to obtain a homogenized ingot.

[0062] 3) Hot extrusion and heat treatment: The homogenized ingot in step 2) is heated and extruded. In the extrusion process, a rod casting furnace is used for preheating and an induction heating furnace is used for heating to an ingot temperature of 460-480°C. The extrusion speed is set at 0.8-1.5 mm / s, and the outlet temperature is set to be greater than 510°C. Then, the ingot is cooled by water cooling, and the water cooling temperature of the water cooling method is ≤50°C. Then, an extruded profile is obtained. The cross-sectional dimensions of the extruded sheet are in the range of: length 70-140 mm, width 8-3 mm, R angle 0.25-1 mm, and aging system: 130-145°C*10-24h.

[0063] 4) Anodizing treatment: ① Degreasing treatment: Use alkaline solution for degreasing, use 40g / L sodium carbonate, 40g / L sodium phosphate, 80g / L sodium pyrophosphate, 0.1g / L OP-10 surfactant content to prepare an alkaline solution, put the product in step 3) into a cleaning tank containing the alkaline solution, raise the temperature of the solution in the cleaning tank to 40-60°C, and set the degreasing time to 3-8 minutes;

[0064] The degreased product is subjected to multiple water washing operations;

[0065] ② Neutralization and light emission: After water washing, put it into a nitric acid cleaning tank with a concentration of ≥100g / 1, set the neutralization reaction time to ≥30s, and operate at room temperature;

[0066] The product after neutralization and light treatment is subjected to multiple water washing operations;

[0067] ③ Anodizing: Use sulfuric acid as the electrolyte and use a constant voltage method for anodizing. Set the voltage in the flow tank to 12-14V, and limit the concentration of aluminum ions to ≦18g / L, the concentration of free H2SO4 to 190-200g / L, set the tank temperature to 20±2°C, and set the oxidation time to 50-60 minutes;

[0068] The product after the above steps is subjected to multiple water washing operations;

[0069] ④ Sealing treatment: Add the washed product into the sealing tank and add the tank liquid, which contains: Ni 2+ :1.05g / l,F - : 0.35g / l, set the bath solution pH to 5.8, and use room temperature sealing. In this step, nickel ions are sealed in the oxide film by hydrolysis. The sealing time is 10 minutes, and the temperature during the sealing process is set to 28-35°C;

[0070] The product after the above sealing treatment is subjected to multiple water washing operations to obtain the final product.

[0071] Embodiment 3:

[0072] A method for preparing an anodizable high-strength 7xxx series aluminum alloy comprises the following steps:

[0073] 1) Melting and casting: ① Melting master alloy: prepare materials according to mass percentage of copper 1.3%, manganese 0.09%, magnesium 2.20%, zirconium 0.01%, zinc 6.35%, titanium 0.013% and the balance of aluminum to obtain smelting metal, wherein zinc, aluminum and magnesium are pure zinc ingots, high-purity low-iron aluminum ingots and pure magnesium ingots, and copper, manganese, zirconium and titanium are aluminum-copper master alloys, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium-boron master alloys; high-purity low-iron aluminum ingots are charged into a furnace, and the furnace gas temperature is set to 750-780°C. After the high-purity low-iron aluminum ingots are melted, slag is removed, and then other master alloys except the aluminum-titanium-boron master alloy and pure magnesium ingot are added and wait for them to be completely melted. After the charge is melted, the temperature is 735-745°C, and after slag removal, pure magnesium ingots are added and stirred;

[0074] ② Raise the temperature to 780-790℃, use high-purity argon and sodium-free refining agent for refining for 10-15 minutes, then skim and let stand;

[0075] ③ After the casting temperature reaches 740-750℃, casting begins, and wire feeding of the Rt-Ti-B master alloy is performed to obtain an ingot;

[0076] Among them, the wire feeding speed of aluminum-titanium-boron master alloy is 1m / min, the water flow rate is 1200L / min, and the water temperature is 28°C. During the casting process, a large amount of water is required for cooling to ensure the formation of the cast rod, and the casting speed is set differently according to different casting specifications. When the cast rod specification is φ292, the casting speed is 50-55mm / min; the specification is φ234, the casting speed is 70-75mm / min; the specification is φ178, the casting speed is 85-90mm / min.

[0077] 2) Homogenization treatment: The ingot in step 1) is homogenized by a homogenization process, and the temperature of the first stage is set to 305°C and the time is 1 hour; the temperature of the second stage is set to 415°C and the time is 2 hours; the temperature of the third stage is set to 467°C and the time is 11 hours; the third stage homogenization is carried out after strong wind cooling to obtain a homogenized ingot.

[0078] 3) Hot extrusion and heat treatment: The homogenized ingot in step 2) is heated and extruded. In the extrusion process, a rod casting furnace is used for preheating and an induction heating furnace is used for heating to an ingot temperature of 460-480°C. The extrusion speed is set at 0.8-1.5 mm / s, and the outlet temperature is set to be greater than 510°C. Then, the ingot is cooled by water cooling, and the water cooling temperature of the water cooling method is ≤50°C. Then, an extruded profile is obtained. The cross-sectional dimensions of the extruded sheet are in the range of: length 70-140 mm, width 8-3 mm, R angle 0.25-1 mm, and aging system: 130-145°C*10-24h.

[0079] 4) Anodizing treatment: ① Degreasing treatment: Use alkaline solution for degreasing, use 48g / L sodium carbonate, 48g / L sodium phosphate, 90g / L sodium pyrophosphate, 0.3g / L OP-10 surfactant content to prepare an alkaline solution, put the product in step 3) into a cleaning tank containing the alkaline solution, increase the temperature of the solution in the cleaning tank to 40-60°C, and set the degreasing time to 3-8 minutes;

[0080] The degreased product is subjected to multiple water washing operations;

[0081] ② Neutralization and light emission: After water washing, put it into a nitric acid cleaning tank with a concentration of ≥100g / 1, set the neutralization reaction time to ≥30s, and operate at room temperature;

[0082] The product after neutralization and light treatment is subjected to multiple water washing operations;

[0083] ③ Anodizing: Use sulfuric acid as the electrolyte and use a constant voltage method to perform anodizing treatment. Set the voltage in the flow tank to 12-14V, and limit the concentration of aluminum ions to ≦18g / L, the concentration of free H2SO4 to between 190-200g / L, set the tank temperature to 20±2°C, and set the oxidation time to 50-60 minutes;

[0084] The product after the above steps is subjected to multiple water washing operations;

[0085] ④ Sealing treatment: Add the washed product into the sealing tank and add the tank liquid, which contains: Ni 2+ :1.2g / l,F - : 0.4g / l, set the bath solution pH to 6, and use room temperature sealing. In this step, nickel ions are sealed in the oxide film by hydrolysis. The sealing time is 15 minutes, and the temperature during the sealing process is set to 28-35°C;

[0086] The product after the above sealing treatment is subjected to multiple water washing operations to obtain the final product.

[0087] Embodiment 4:

[0088] A method for preparing an anodizable high-strength 7xxx series aluminum alloy comprises the following steps:

[0089] 1) Melting and casting: ① Melting master alloy: prepare materials according to mass percentage of copper 1.5%, manganese 0.1%, magnesium 2.35%, zirconium 0.012%, zinc 6.35%, titanium 0.01% and the balance aluminum to obtain smelting metal, wherein zinc, aluminum and magnesium are pure zinc ingots, high-purity low-iron aluminum ingots and pure magnesium ingots, and copper, manganese, zirconium and titanium are aluminum-copper master alloys, aluminum-manganese master alloys, aluminum-zirconium master alloys and aluminum-titanium-boron master alloys; high-purity low-iron aluminum ingots are charged into a furnace, and the furnace gas temperature is set to 750-780°C. After the high-purity low-iron aluminum ingots are melted, slag is removed, and then other master alloys except the aluminum-titanium-boron master alloy are added and wait for them to be completely melted. After the charge is melted, the temperature is 735-745°C, and after slag removal, pure magnesium ingots are added and stirred;

[0090] ② Raise the temperature to 780-790℃, use high-purity argon and sodium-free refining agent for refining for 10-15 minutes, then skim and let stand;

[0091] ③ After the casting temperature reaches 740-750℃, casting begins, and wire feeding of the Rt-Ti-B master alloy is performed to obtain an ingot;

[0092] Among them, the wire feeding speed of aluminum-titanium-boron master alloy is 1.2m / min, the water flow rate is 1200L / min, and the water temperature is 28°C. During the casting process, a large amount of water is required for cooling to ensure the formation of the cast rod, and the casting speed is set differently according to different casting specifications. When the cast rod specification is φ292, the casting speed is 50-55mm / min; the specification is φ234, the casting speed is 70-75mm / min; the specification is φ178, the casting speed is 85-90mm / min.

[0093] 2) Homogenization treatment: The ingot in step 1) is homogenized by a homogenization process, and the temperature of the first stage is set to 320°C and the time is 1.5 hours; the temperature of the second stage is set to 420°C and the time is 2 hours; the temperature of the third stage is set to 470°C and the time is 12 hours; the third stage homogenization is carried out after strong wind cooling to obtain a homogenized ingot.

[0094] 3) Hot extrusion and heat treatment: The homogenized ingot in step 2) is heated and extruded. In the extrusion process, a rod casting furnace is used for preheating and an induction heating furnace is used for heating to an ingot temperature of 460-480°C. The extrusion speed is set at 0.8-1.5 mm / s, and the outlet temperature is set to be greater than 510°C. Then, the ingot is cooled by water cooling, and the water cooling temperature of the water cooling method is ≤50°C. Then, an extruded profile is obtained. The cross-sectional dimensions of the extruded sheet are in the range of: length 70-140 mm, width 8-3 mm, R angle 0.25-1 mm, and aging system: 130-145°C*10-24h.

[0095] 4) Anodizing treatment: ① Degreasing treatment: Use alkaline solution for degreasing, use 50g / L sodium carbonate, 40g / L sodium phosphate, 100g / L sodium pyrophosphate, 0.3g / L OP-10 surfactant content to prepare an alkaline solution, put the product in step 3) into a cleaning tank containing the alkaline solution, raise the temperature of the solution in the cleaning tank to 40-60°C, and set the degreasing time to 3-8 minutes;

[0096] The degreased product is subjected to multiple water washing operations;

[0097] ② Neutralization and light emission: After water washing, put it into a nitric acid cleaning tank with a concentration of ≥100g / 1, set the neutralization reaction time to ≥30s, and operate at room temperature;

[0098] The product after neutralization and light treatment is subjected to multiple water washing operations;

[0099] ③ Anodizing: Use sulfuric acid as the electrolyte and use a constant voltage method to perform anodizing treatment. Set the voltage in the flow tank to 12-14V, and limit the concentration of aluminum ions to ≦18g / L, the concentration of free H2SO4 to between 190-200g / L, set the tank temperature to 20±2°C, and set the oxidation time to 50-60 minutes;

[0100] The product after the above steps is subjected to multiple water washing operations;

[0101] ④ Sealing treatment: Add the washed product into the sealing tank and add the tank liquid, which contains: Ni 2+ :1.4g / l,F - : 0.4g / l, set the bath pH to 6.2, and use room temperature sealing. In this step, nickel ions are sealed in the oxide film by hydrolysis. The sealing time is 20 minutes, and the temperature during the sealing process is set to 28-35°C;

[0102] The product after the above sealing treatment is subjected to multiple water washing operations to obtain the final product.

[0103] According to the above embodiment, the following data are obtained and plotted into Table 1

[0104] Table 1 Sensory evaluation results of different embodiments of finished products of high-strength 7xxx series aluminum alloys

[0105]

[0106] It can be concluded from the above test data that the 7xxx series aluminum alloy prepared by the method of the present invention has a high-strength effect that can be anodized, and has good intergranular corrosion and exfoliation corrosion resistance; in terms of alloy properties, it can achieve: tensile strength ≥480MPa, yield strength ≥450MPa, elongation ≥9%; in the profile grain size, the average grain size ≤150μm, the maximum grain size ≤250μm; and after anodizing treatment, the polishing gloss reaches >450GU, and after oxidation film formation, the surface of the sample has no fogging, numbness, or discoloration, which avoids the yellowing of the anodized color. Compared with the traditional 6xxx series aluminum alloy, it has more obvious advantages and has a good market prospect.

[0107] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An anodizable high-strength 7xxx series aluminum alloy, characterized in that: The anodizable high-strength 7xxx series aluminum alloy comprises the following components: Silicon <0.07%, iron ≤0.12%, copper 1.2-1.6%, manganese 0.07-0.17%, magnesium 2.10-2.40%, zirconium 0.003-0.012%, zinc 6.2-6.5%, titanium 0.003-0.020%, and the balance is aluminum and other inevitable impurity elements; the total mass of other inevitable impurity elements does not exceed 0.15% of the total mass of the alloy.

2. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 1, wherein: The process includes the following steps: 1) Melting and casting: ① Melting master alloy: Prepare materials according to the mass percentage of silicon <0.07%, iron ≤0.12%, copper 1.2-1.6%, manganese 0.07-0.17%, magnesium 2.10-2.40%, zirconium 0.003-0.012%, zinc 6.2-6.5%, titanium ≤0.003-0.020% and the balance is aluminum to obtain smelting metal, wherein zinc, aluminum and magnesium are pure zinc ingots, high-purity low-iron aluminum ingots and pure Magnesium ingots, copper, manganese, zirconium and titanium use aluminum-copper master alloy, aluminum-manganese master alloy, aluminum-zirconium master alloy and aluminum-titanium-boron master alloy; high-purity low-iron aluminum ingots are loaded into the furnace, and the furnace gas temperature is set to 750-780°C. After the high-purity low-iron aluminum ingots are melted, slag is removed, and then other master alloys except aluminum-titanium-boron master alloy and pure magnesium ingots are added and wait for them to be completely melted. After the charge is melted, the temperature is 735-745°C. After slag removal, pure magnesium ingots are added and stirred; ② Raise the temperature to 780-790℃, use high-purity argon and sodium-free refining agent for refining for 10-15 minutes, then skim and let stand; ③ After the casting temperature reaches 740-750°C, casting begins, and aluminum-titanium-boron master alloy wire is fed to obtain an ingot; 2) Homogenization treatment: the ingot in step 1) is homogenized by a homogenization process, the temperature of the first stage is set to 300-320°C, the time is 1-2h; the temperature of the second stage is set to 400-420°C, the time is 1-2h; the temperature of the third stage is set to 460-480°C, the time is 10-12h; the third stage homogenization is carried out after strong wind cooling to obtain a homogenized ingot, the average grain size of the cast rod structure is ≤150μm, and the maximum grain size is ≤200μm; 3) Hot extrusion and heat treatment: The homogenized ingot in step 2) is heated and extruded. In the extrusion process, the ingot temperature is 460-480°C using a rod casting furnace for preheating and an induction heating furnace. The extrusion speed is set at 0.8-1.5 mm / s, and the outlet temperature is set to be greater than 510°C. The extrusion is then cooled by water cooling to obtain an extruded profile. The cross-sectional dimensions of the extruded sheet are as follows: 70-140 mm in length, 8-3 mm in width, and 0.25-1 mm in R angle. 4) Anodizing treatment: ① Degreasing treatment: Use alkaline solution for degreasing, use 40-50g / L sodium carbonate, 40-50g / L sodium phosphate, 80-100g / L sodium pyrophosphate, 0.1-0.5g / L OP-10 surfactant content to prepare an alkaline solution, put the product in step 3) into a cleaning tank containing the alkaline solution, raise the temperature of the solution in the cleaning tank to 40-60°C, and set the degreasing time to 3-8 minutes; The degreased product is subjected to multiple water washing operations; ② Neutralization and light extraction: After water washing, put it into a nitric acid cleaning tank with a concentration of ≥100g / l, set the neutralization reaction time to ≥30s, and operate at room temperature; The product after neutralization and light treatment is subjected to multiple water washing operations; ③ Anodizing: Use sulfuric acid as the electrolyte and use a constant voltage method for anodizing. Set the voltage in the flow tank to 12-14V, and limit the concentration of aluminum ions to ≦18g / L, the concentration of free H2SO4 to between 190-200g / L, set the tank temperature to 20±2℃, and set the oxidation time to 50-60 minutes; The product after the above steps is subjected to multiple water washing operations; ④ Sealing treatment: Add the washed product into the sealing tank and add the tank liquid, which contains: Ni 2+ :1.05-1.45g / l,F - : 0.35-0.50g / l, set the bath solution pH to 5.8-6.4, and use room temperature sealing. In this step, nickel ions are hydrolyzed in the oxide film to seal the holes; The product after the above sealing treatment is subjected to multiple water washing operations to obtain the final product.

3. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 2, characterized in that: in, In step 1), the wire feeding speed of the aluminum-titanium-boron master alloy is 0.8-1.2 m / min, the water flow rate is 1000-1500 L / min, and the water temperature is 25-30°C.

4. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 3, characterized in that: in, In step 1), the casting speed is set differently according to different casting specifications. When the casting rod specification is φ292, the casting speed is 50-55mm / min; when the specification is φ234, the casting speed is 70-75mm / min; when the specification is φ178, the casting speed is 85-90mm / min.

5. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 3 or 4, characterized in that: in, In step 3), the water cooling temperature of the water cooling method is ≤50°C, and the aging system is: 130-145°C*10-24h.

6. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 5, characterized in that: in, The temperature of sulfuric acid in step 4) is controlled within 20±2° C., and the reaction time of this step is 50-60 min.

7. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 6, characterized in that: in, In the sealing treatment operation, the sealing time is set to 10-20 minutes, and the temperature during the sealing process is set to 28-35°C.

8. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 6, characterized in that: in, After hot extrusion and heat treatment, the tensile strength of the profile is ≥480MPa, the yield strength is ≥450MPa, and the elongation is ≥9%.

9. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 8, characterized in that: in, After hot extrusion and heat treatment, the average grain size of the profile is ≤150 μm, and the maximum grain size is ≤250 μm.

10. The method for preparing an anodizable high-strength 7xxx series aluminum alloy according to claim 9, characterized in that: In step 4), the surface gloss of the profile after anodizing treatment needs to reach 450-500GU; after oxidation film formation, the film thickness needs to reach 8-15μm, and the surface of the sample is not foggy, numb, or discolored to be qualified.

Citation Information

Cited By

  • Sewage treatment method for efficiently removing phosphorus and heavy metals based on electric flocculation technology

    CN121063653A

  • A high-efficiency phosphorus and heavy metal removal method for sewage treatment based on electrocoagulation technology

    CN121063653B